Tomáša Halíka myśli o współczesnym Kościele : Tomáš Halík thinks about the contemporary Church - Artemiuk, Przemysław (Studia Teologiczne Białystok Drohiczyn Łomża, 2022)
The article presents T. Halík's thoughts on the Church in the time of the pandemic and after the pandemic. The Czech theologian, like Gottfried Wilhelm Leibniz, presents his own theodicy. It is definitely different from the eighteenth century one. The world is also different, and so are we. Fortunately, God does not change, neither then nor today. T. Halík knows this very well, therefore he stands with his camera inside the empty church of St. Salwator in the Old Town of Prague. He wants to guide his viewers from Ash Wednesday to Pentacost. The Time of Empty Churches is a collection of seventeen sermons. These are not just biblical interpretations of liturgical texts. Halík is inspired by the Gospel and builds narratives full of theological depth. Let us reach for the most intriguing threads of this work. Catholicism is changing before our eyes. This is, by no means, the end of the Church. Theologians, philosophers and journalists, who analyse these changes, all agree on this point. Yet, the essence of faith remains unchanged. It is the Catholic imaginarium, to which the world has been used for centuries, is falling apart. The Gospel ceases to rule countries. Christians, on the other hand, are invited to go towards the source.